2019
DOI: 10.1155/2019/1905416
|View full text |Cite
|
Sign up to set email alerts
|

Study on the Potential Biomarkers of Maternal Urine Metabolomics for Fetus with Congenital Heart Diseases Based on Modified Gas Chromatograph-Mass Spectrometer

Abstract: Background. There has been significant research on the genetic and environmental factors of congenital heart defects (CHDs), but few causes of teratogenicity, especially teratogenic mechanisms, can be clearly identified. Metabolomics has a potential advantage in researching the relationship between external factors and CHD. Objective. To find and identify the urinary potential biomarkers of pregnancy (including in the second and third trimesters) for fetuses with CHD based on modified gas chromatograph-mass sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 31 publications
1
17
0
Order By: Relevance
“…Graca et al ( 16 , 17 ) did not find changes in proline and uric acid levels in AF when using MRI to detect fetal malformations, including CHD. However, the changes in uric acid were consistent with the urine biomarker reported by Xie et al ( 19 ), as shown in Table 1 . Our results using AF were not consistent with those obtained using the maternal serum in early pregnancy reported by Bahado-Singh et al ( 18 ) and our own results in maternal serum.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Graca et al ( 16 , 17 ) did not find changes in proline and uric acid levels in AF when using MRI to detect fetal malformations, including CHD. However, the changes in uric acid were consistent with the urine biomarker reported by Xie et al ( 19 ), as shown in Table 1 . Our results using AF were not consistent with those obtained using the maternal serum in early pregnancy reported by Bahado-Singh et al ( 18 ) and our own results in maternal serum.…”
Section: Discussionsupporting
confidence: 90%
“…Several metabolomics studies have focused on fetal CHD, and we summarized these studies as shown in Table 1. In these studies, the types of samples used were maternal serum, maternal urine and amniotic fluid (AF), and the methods used were direct injection/liquid chromatography and tandem mass spectrometry (DI/LC-MS/MS), tandem mass spectrometry (MS/MS), gas chromatography-mass spectrometry (GC-MS) and nuclear magnetic resonance (NMR) (16)(17)(18)(19)(20). However, studies of fetal CHD based on amniotic fluid metabolomics remains limited due to the availability of AF.…”
Section: Introductionmentioning
confidence: 99%
“…In terms of metabolomic methods, a total of 2472 metabolites were identi ed using the UHPLC-QTOF-MS untargeted metabolomics detection in this study. Many new metabolites were found compared to previous studies, which mostly used NMR or GC-TOF-MS methods, could only detect hundreds of metabolites [15][16][17][18] . UHPLC increasingly displacing conventional high performance liquid chromatography 23 LC-MS is the main workhorse of metabolomics owing to its high degree of analytical sensitivity and speci city when measuring diverse chemistry in complex biological samples 24 .…”
Section: Discussionmentioning
confidence: 99%
“…Metabolites 2022, 12, 100 2 of 16 This is particularly important, as disrupted metabolism related to the affected birth could impact long-term maternal health. Women with pregnancies affected by CHD have been reported with altered metabolic profiles and were associated with dysregulated metabolic pathways [7][8][9][10]. These markers were often utilized as predictive markers for fetuses with congenital heart defects.…”
Section: Congenital Heart Defects (Chds) Affect Approximately 1% Of A...mentioning
confidence: 99%